ALGEBRA OF HYPER-ANALYTIC FUNCTIONS AS A β-UNIFORM ALGEBRA - Khudoyan, T.M. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2013)
The present paper is devoted to the β-uniform algebra of bounded generalized analytic functions on the “generalized disk”. The issues related to the well-known corona problem for this topological algebra are investigated.